Investigations on momentum distributions and disorder in strongly out-of-equilibrium trapped Bose gases - Vivanco, Franklin Adán Julca (2017)
From almost one century, Bose-Einstein condensation has become progressively more important especially due to its connection with superfluidity, superconductivity and manybody physics. Nowadays quantum gases are powerful experimental tools to discover new physics and to emulate systems in condensed matter due to their versatility and very high control. Despite the increasing use of quantum gases as platforms for studying many problems in physics, their comprehension is very limited if we consider systems that are out-of-equilibrium due to the lack of experimental controllability of all the parameters involved in these systems. Another limitation in the understanding of this kind of systems comes from the limitation of the theoretical frameworks used to understand non-equilibrium dynamics, although many efforts have been made in this direction. Hence, many interesting phenomena in non-equilibrium quantum systems have not yet been discovered or well understood from a theoretical and experimental point of view, and thus its physics have not been the focus of much attention, although this situation has recently changed due to the rapid development of experimental techniques which enables a better control of parameters of these systems. Motivated by this progress, we study non-equilibrium Bose gases in the search of turbulence using an oscillatory excitation performed in a Bose-Einstein condensate of 87Rb atoms. In this thesis, we describe these experiments and characterize our non-equilibrium quantum system through some quantifiers. One of these quantifiers is a dimensionless value that represent the exponent γ obtained from the cascade of the transverse momentum distribution ñ(k). ñ(k) is obtained from absorption images of atoms in expansion using the time-of-flight technique in a well defined range of momenta. We analyze the dependence of γ with the amount of the pumped energy, and we found a steady-value which describe a well-established non-equilibrium regime. Also, it is analyzed the viability of using the fluctuations statistics in order to extract some quantifier from the power-spectrum of the fluctuations assuming that it represents an analog to the energy spectrum, due to the consideration of the time-of-flight technique. From the powerspectrum it is extracted an exponent, in the same range as for ñ(k), and compared with γ 2, that will be the exponent for the pseudo-energy spectrum in the kinetic dominated regime. Finally, we consider, again with the time-of-flight technique, the continuous Shannon entropy as quantifier that measure the disorder of the excited clouds and study their dependence with the pumped energy. These studies show us that there is an out-ofequilibrium regime that takes place when we inject a fixed quantity of energy into the system.